Efficacy of Ethylenediamine Tetraacetic Acid and Calcium Hydroxide in the Removal of Root Canal Filling During Retreatment - Esra Pamukçu Güven (Cumhuriyet University, 2017)
Objective: To compare the effect of Ethylenediamine tetraacetic acid (EDTA) and calcium hydroxide [Ca(OH)2] in the removal of root canal filling material during retreatment procedure. Methodology: Eighty extracted, single-rooted human teeth were used. Root canals were shaped with a crown-down technique using Ni-Ti rotary instruments (ProTaper, Dentsply Maillefer, Switzerland) and filled with a cold lateral condensation method. AH Plus was used as a sealer. After filling, the teeth were divided into 4 groups and root fillings were removed by ProTaper Universal rotary retreatment system. In each group different irrigation and disinfection protocols were followed; Group I. Sodium hypochlorite (5.25%) + EDTA (17%-1 min.) Group II. Sodium hypochlorite (5.25%) Group III. Sodium hypochlorite (5.25%) + Ca (OH)2 Group IV. Sodium hypochlorite (5.25%) + Ca(OH)2 + EDTA (17%-1 min.). Irrigation with 17% EDTA was performed only before D3-Retreatment instrumentation in all groups. AutoCAD system was used to detect the amount of residual root canal filling material. The results were statistically analyzed by SPSS (Statistical Package for Social Sciences) for Windows 15.0, one way ANOVA and Tukey's HSD tests. The significance was evaluated at the level of p<0.05. Results: The amount of the remnant filling material in the root canals retreated in Group I was less than the amount of the material in Group II (p<0.01) and Group III (p<0.05). There was no significant difference observed between the other groups in terms of the quantity of the remnant root canal filling materials (p>0.05). Conclusions: Irrigating the canals with EDTA enhanced the removal of root canal filling during retreatment. However, disinfecting the canals with Ca(OH)2 had no effect in the removal of filling material. Keywords: Retreatment, Sodium Hypochlorite, Ethylenediamine tetraacetic acid, calcium hydroxide.